Inadequate Vaccine Responses in Children With Multiple Sclerosis - Santoro, Jonathan D.; Saucier, Laura E.; Tanna, Runi; Wiegand, Sarah E.; Pagarkar, Dania; Tempchin, Adam F.; Khoshnood, Mellad; Ahsan, Nusrat; Van Haren, Keith (Frontiers in Pediatrics, 2021)
Objective: Immunizations against Hepatitis B virus (HBV) and Varicella Zoster virus (VZV), are recommended for patients with pediatric onset multiple sclerosis (POMS) and may be required prior to initiation of some disease modifying therapies. However, the efficacy of routine vaccine administration in POMS has never been studied. We sought to assess the humoral mediated vaccine response to HBV and VZV in children with POMS. Methods: A multi-center retrospective chart-based review of 62 patients with POMS was performed. Clinical data and antibody titers against HBV and VZV were collected prior to initiation of disease modifying therapy or steroids and compared to institutional control data, using t-test and chi squared analysis. Results: There were low rates of immunity against both HBV and VZV (33% and 25% respectively) among individuals with POMS. Fifteen individuals (24%) were non-immune to both. Compared to institutional control data, individuals with POMS were significantly less likely to be immune to and HBV (p=0.003, 95%CI: 0.22-0.75) and VZV (p<0.001, 95%CI: 0.09-0.39). Interpretation: Individuals with POMS have low rates of antibody-mediated immunity against HBV and VZV, despite receiving the appropriate vaccinations. This suggests an association between POMS and systemic immune dysregulation although further study is needed.